Mencari Konsep Wajah Sistem Hukum Nasional: Studi Tentang Polemik dan Tantangan Penegakan Hukum Progresif dalam Sistem Hukum Indonesia - Rayno Dwi Adityo (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
Law for the human, not contrary and the law is expected to respond tocommunity needs. An idea where the law required to continue growing and dynamic,providing a sense of justice for people. Until now, both are hampered by internaldevelopment of national law that explicitly do tend to the civil law rather than commonlaw, althought many who argue that Indonesia is not on these two legal system. Thepattern of diversity due to factor that also affect the archipelagic state the rules stylepluralistic norm and regulations that where born from a logical consequence of ethnicdiversity in a plural society. Demand urgency the law enforcement and strengtheningjustice.